Religiosity and Social Support as Determinants of Death Anxiety Among the Elderly: Kekuatan Keagamaan dan Dukungan Sosial sebagai Faktor Penentu Kecemasan Kematian di Kalangan Lansia - Haq, Izzul; Mariyati, Lely (Indonesian Journal of Islamic Studies, 2025)
Background: Death anxiety is a psychological challenge frequently experienced by the elderly, often associated with feelings of helplessness and fear. Specific Background: Religiosity and social support are considered key protective factors that may reduce such anxiety. Knowledge Gap: Few studies have analyzed the combined role of religiosity and social support on death anxiety in elderly populations living in communal facilities. Aim: This study aims to examine the simultaneous and partial roles of religiosity and social support in reducing death anxiety among the elderly. Results: Multiple regression analysis on 100 respondents showed that religiosity and social support jointly explained 27.2% of the variance in death anxiety. Social support contributed the largest effective portion (14.8%), followed by religiosity (12.3%). Novelty: The study highlights the significance of combining religious engagement with social support interventions to address psychological distress in elderly groups. Implications: The findings suggest the need for integrated spiritual and social programs to promote emotional well-being and prepare the elderly for end-of-life acceptance. Highlights : Religiosity and social support reduce death anxiety Social support contributes more than religiosity Practical implications for elderly care programs Keyword: Religiosity, Social Support, Death Anxiety, Elderly, Psychology